Sticking and tipping points: a case study of preschool education policy and practice in Astana, Kazakhstan. Issue 3 (4th May 2018) - Needham, Martin; Kuleimenov, Daurenbek; Soltanbekova, Arailym
ABSTRACT: This article presents a case study exploring how national guidance for kindergartens in Kazakhstan was interpreted in practice. Document analysis of the State Education Standards of Preschool Upbringing and Education, together with stakeholder interviews and observations of six Astana kindergarten settings, illustrates how competing perspectives on preparing children for school can both promote and limit opportunities for child-led activity in early education. The article considers postcolonial and neocolonial pasts and their potential to influence the present, identifying potential sticking points that may limit change processes. The article suggests processes for building locally grounded praxis in order to create tipping points where child-initiated pedagogy could become a more frequent feature of practice.